Disorders of pigmentation: melanoma - Fisher, David E. (Henry Stewart Talks, 2014)
Melanocyte development, key factors regulating lineage development, relationships to pigmentation diseases, MITF, IV-induced pigmentation, melanoma-genesis, melanoma oncogene discovery, BRAF-targeted therapy, immunotherapy, red pigment and melanoma-genesis.